Biology and ecology of sardines and anchovies - Ganias, Konstantinos (2014)
"Biology and Ecology of Sardines and Anchovies and ecology. Chapter five by M. Giannoulaki et al. describes the spatial distribution and the habitat characteristics of anchovies and sardines in the main upwelling areas particularly focusing on ecosystems that are seldom tackled like the Mediterranean and the Black Sea and the Australian waters. Chapter six by I. Katara discusses some dominant recruitment theories, their relation to small pelagic fish variability, as well as some hypotheses that arose from the observation of phenomena characteristic of sardine and anchovy populations. The third section covers the socioeconomic impact of sardine and anchovy fisheries around the world oceans and provides several case studies on their exploitation status and management. Chapter seven by G. Merino et al. describes the role of anchovies and sardines as reduction fisheries in the world fishmeal production and overviews the interaction between the resource and environmental and socioeconomic drivers. Chapter eight by N. Lo and B. Fissel reviews assessment methods of anchovy and sardine stocks in the U.S. focusing on the daily egg production method (DEPM). Finally chapter nine by C. Pitta et al. summarizes some socioeconomic and management aspects of sardine and anchovy fisheries worldwide and the future challenges and opportunities for these fisheries"--
Keywords: Sardines -- Ecology; Anchovies -- Ecology; Sardines -- Geographical distribution; Anchovies -- Geographical distribution; SCIENCE / Life Sciences / Biology / Marine Biology